Papa's song - McMullan, Kate.; McMullan, Jim, 1936- (New York : Farrar Straus Giroux, 2000)
After Grandma, Grandpa, and Mama Bear unsuccessfully try to sing Baby Bear to sleep, Papa finds just the right song.
Adult 520
Accelerated Reader AR
Keywords: Bears -- Fiction; Babies -- Fiction; Sleep -- Fiction; Father and child -- Fiction